Prolonged fecal shedding of SARS‐CoV‐2 in a young immunocompetent COVID‐19 patient: A case report and literature overview - Xiao, Fang; Wan, Peiqi; Wei, Qiuling; Wei, Guiyang; Yu, Yanhong (Journal of medical virology, 2022)
Clinicians are facing several challenges in tackling coronavirus disease 2019 (COVID‐19); one issue is prolonged detection of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) RNA. Here, we describe a case of SARS‐CoV‐2 infection in a young immunocompetent patient with a virological course lasting for 71 days. Following antiviral treatment, but no additional glucocorticoid or interferon therapy, the patient recovered from COVID‐19 pneumonia (moderate). Detection of viral RNA via throat swabs showed negative results. However, the viral RNA reappeared and persisted in stool samples for an additional 27 days, while the patient remained asymptomatic and exhibited no abnormal signs. This case indicates that SARS‐CoV‐2 can result in a prolonged fecal RNA shedding, even in an immunocompetent patient with zero exposure to immunosuppressive therapies.